2009
DOI: 10.2337/dc08-2011
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Inflammation and Diabetic Polyneuropathy

Abstract: OBJECTIVE Subclinical inflammation represents a risk factor of type 2 diabetes and several diabetes complications, but data on diabetic neuropathies are scarce. Therefore, we investigated whether circulating concentrations of acute-phase proteins, cytokines, and chemokines differ among diabetic patients with or without diabetic polyneuropathy. RESEARCH DESIGN AND METHODS We measured 10 markers of subclinical inflammation in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
75
1
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(94 citation statements)
references
References 15 publications
11
75
1
7
Order By: Relevance
“…In that study, patients with painful neuropathy had higher circulating levels of CRP and sICAM-1, whereas no differences were found for TNF-a, and IL-6 was not measured (10). The difference compared with our study regarding CRP is interesting given that we previously found associations between CRP and the MNSI score in a sample of diabetic patients (17), but not in the general older population (13), which suggests differences in risk factors of DSPN with respect to diabetic status. One study reported an association between TNF-a plasma levels and neuropathic pain in patients with type 2 diabetes, but the analysis was not adjusted for any confounding variables (18).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…In that study, patients with painful neuropathy had higher circulating levels of CRP and sICAM-1, whereas no differences were found for TNF-a, and IL-6 was not measured (10). The difference compared with our study regarding CRP is interesting given that we previously found associations between CRP and the MNSI score in a sample of diabetic patients (17), but not in the general older population (13), which suggests differences in risk factors of DSPN with respect to diabetic status. One study reported an association between TNF-a plasma levels and neuropathic pain in patients with type 2 diabetes, but the analysis was not adjusted for any confounding variables (18).…”
Section: Discussioncontrasting
confidence: 51%
“…The population-based sample and the adjustment for multiple confounding variables represent strengths of our analysis. The population-based approach is relevant because DSPN without and with pain also affects a considerable proportion of nondiabetic individuals among the older population, as previously reported (3,6,17) and reviewed (2). A detailed analysis of this intriguing finding is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 92%
“…After an injury, such as those triggered by hyperglycaemia or modified LDLs, intracellular cascades can be activated in Schwann cells, including nuclear translocation of NF-κB and consequent expression of various cytokines and chemokines, similar to the scenario after traumatic nerve damage. These events contribute to Wallerian degeneration and emphasize the potential involvement of Schwann cells in the subclinical inflammation that is observed in patients with type 2 diabetes and is detectable as increased circulating levels of C-reactive protein and IL-6, which are consistently associated with polyneuropathy 95 . Furthermore, via production of cytokines and chemokines, Schwann cells might contribute to immune cell recruitment 4,96 and nerve inflammation in diabetes.…”
Section: Oxidative Stress and Mitochondrial Dysfunctionmentioning
confidence: 87%
“…Several population-based studies conducted in different KORA cohorts have documented associations between markers of systemic subclinical inflammation and the presence of DSPN [89][90][91][92]. In the KORA F3 cohort, high levels of C-reactive protein (CRP) and interleukin 6 (IL-6) were positively associated with the presence and severity of DSPN [92].…”
Section: Inflammationmentioning
confidence: 99%
“…In the KORA F3 cohort, high levels of C-reactive protein (CRP) and interleukin 6 (IL-6) were positively associated with the presence and severity of DSPN [92]. In the KORA F4 cohort, serum concentrations of the anti-inflammatory IL-1 receptor antagonist (IL-1RA), IL-6, IL-18, and soluble intercellular adhesion molecule-1 (sICAM-1) were positively associated with the severity of neuropathic deficits, suggesting that DSPN is linked to proinflammatory and anti-inflammatory, possibly compensatory, processes in the older general population [91].…”
Section: Inflammationmentioning
confidence: 99%